1991
DOI: 10.1111/j.1365-2125.1991.tb05555.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of protein containing meals on the pharmacokinetics of levodopa in healthy volunteers.

Abstract: 1. The pharmacokinetics of levodopa and paracetamol after single oral doses have been investigated in eight healthy young volunteers in the fasted state and following isocaloric meals containing either 10.5 g or 30.5 g of protein. 2. The initial peak and maximum plasma drug concentrations and the times at which these occurred were not affected by food. 3. The mean area under the plasma concentration‐time curve (AUC) for paracetamol following an overnight fast did not differ significantly from that observed fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
2

Year Published

1993
1993
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 19 publications
1
21
2
Order By: Relevance
“…Nevertheless, the intestinal absorption of levodopa was not blocked entirely despite a high luminal concentration of L-leu. This, together with the observation that a protein-rich diet has no effect on the plasma concentrations of levodopa (Frankel et al, 1989;Robertson et al, 1991;Tsui et al, 1989) suggests that levodopa is partly absorbed by passive diffusion across the intestinal mucosa, probably by the paracellular route. This hypothesis has support in the fact that levodopa is a small and hydrophilic molecule and that the jejunal epithelia is more leaky than the tight epithelium of the rectum, where no absorption of levodopa has been demonstrated (Eisler et al, 1981;Schultz, 1981).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nevertheless, the intestinal absorption of levodopa was not blocked entirely despite a high luminal concentration of L-leu. This, together with the observation that a protein-rich diet has no effect on the plasma concentrations of levodopa (Frankel et al, 1989;Robertson et al, 1991;Tsui et al, 1989) suggests that levodopa is partly absorbed by passive diffusion across the intestinal mucosa, probably by the paracellular route. This hypothesis has support in the fact that levodopa is a small and hydrophilic molecule and that the jejunal epithelia is more leaky than the tight epithelium of the rectum, where no absorption of levodopa has been demonstrated (Eisler et al, 1981;Schultz, 1981).…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, competition for absorption between levodopa and amino acids derived from dietary proteins is possible and, accordingly, protein-restricted diets form part of the therapy of Parkinson's disease (Riley & Lang, 1988). However, this potential interaction in the absorption of levodopa does not seem to result in a significant decrease in the plasma concentrations of levodopa after oral administration (Frankel et al, 1989;Robertson et al, 1991;Tsui et al, 1989). Therefore, it has also been suggested that amino acids in the blood decrease the transport of levodopa across the blood-brain barrier, (Frankel et al, 1989;Tsui et al, 1989;Wade & Katzman, 1975), thereby offsetting any decrease in plasma drug concentration resulting from impaired absorption.…”
mentioning
confidence: 99%
“…Studies show that a diet high protein consumption may reduce the levodopa bioavailability, showing the interaction drug/food (8,24,25,(27)(28)(29). However, Robertson et al (30) ensure that there is no amino acids interference in the intestinal absorption of levodopa, and suggest that the interference occurs only in competing for blood brain barrier. It is similar to study of Simon et al (26) which asserts that the protein may have a little effect on the intestine absorption of levodopa and it is most likely the aminoacid/drug competition to entry into the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Degradation of levodopa in the systemic circulation and competition with levodopa metabolites over the BBB results in lower levodopa levels in the brain. High protein-containing meals have also been shown to impair the clinical effect of levodopa and it might also be caused by the increased competition across the BBB where levodopa and other LNAAs share the same transport system (63)(64)(65). In the brain levodopa is metabolized to DA by AADC in dopaminergic neurons and the dopaminergic neurons autoregulate the release of DA in a healthy person resulting in smooth DA levels in the brain.…”
Section: Levodopa In the Brainmentioning
confidence: 99%